Fenomena Kenakalan Remaja Pada Aktivitas Geng Motor di desa Melati Ii Kecamatan Perbaungan - Rahmadani, Riski; Jailani, Muhammad (Mahesa Research Center, 2024)
This study aims to describe and analyze the phenomenon of juvenile delinquency in motorcycle gang activities in Melati II Village, Perbaungan District. This study uses a qualitative research method with a phenomenological approach. Data collection techniques used in this study through observation, interviews, and documentation. The results of the study indicate that the phenomenon of juvenile delinquency in motorcycle gang activities in Melati II Village, Perbaungan District is related to internal and external factors of adolescents. Internal factors include the desire to be recognized, self-identity, and the search for identity. External factors include the influence of the family environment, social circles, and lack of youth infrastructure. Forms of juvenile delinquency carried out by motorcycle gang members include illegal racing, brawls, drinking alcohol, and drug abuse. The impact of these motorcycle gang activities has disturbed the community and has the potential to cause security disturbances, so that many people submit complaints to the village government to request efforts from the village. Efforts made to overcome this problem are through fostering and empowering adolescents, as well as increasing cooperation between families, schools, and the community.